2016
DOI: 10.1017/jfm.2016.131
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Saffman–Taylor fingers to channel-depth perturbations

Abstract: We examine the sensitivity of Saffman-Taylor fingers to controlled variations in channel depth by investigating the effects of centred, rectangular occlusions in Hele-Shaw channels. For large occlusions, the geometry is known to support symmetric, asymmetric and oscillatory propagation states when air displaces a more viscous fluid from within the channel. A previously developed depth-averaged model is found to be in quantitative agreement with laboratory experiments once the aspect ratio (width/height) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(78 citation statements)
references
References 33 publications
9
69
0
Order By: Relevance
“…If we repeat this analysis for the contribution associated with the singularity at ζ = −i/q, we can determine the equivalent late-order terms and Stokes switching behaviour associated with χ L . In this case, we find that F (ζ) is also given by (20), and that the Stokes switching occurs across a different Stokes line, satisfying Im[χ L ] = 0 with the condition that Re[χ L ] = 0. This curve is also studied in more detail in Section 5, and it is found that the contribution is switched as the curve is crossed from the negative side to the positive side.…”
Section: Discussionmentioning
confidence: 85%
“…If we repeat this analysis for the contribution associated with the singularity at ζ = −i/q, we can determine the equivalent late-order terms and Stokes switching behaviour associated with χ L . In this case, we find that F (ζ) is also given by (20), and that the Stokes switching occurs across a different Stokes line, satisfying Im[χ L ] = 0 with the condition that Re[χ L ] = 0. This curve is also studied in more detail in Section 5, and it is found that the contribution is switched as the curve is crossed from the negative side to the positive side.…”
Section: Discussionmentioning
confidence: 85%
“…As a result, the effects of the compliance-induced taper are diminished and the flow is dominated by viscous dissipation within the wedge [see figure 4(c)]. The asymmetric fingers at low Ca arise because of the central constriction of the channel ahead of the interface, which is associated with the quartic profile of the collapsed membrane in the transverse cross-section (Ducloué et al 2017b); asymmetric fingers minimise viscous dissipation in rigid channels of similar geometry (Franco-Gómez et al 2016). The contrast between peeling modes is further illustrated in figure 4(c); here the total pressure drop within the oil is given by the difference between the bubble pressure p B and the hydrostatic pressure head p HS far ahead of the interface, which sets the initial collapse.…”
Section: Resultsmentioning
confidence: 99%
“…The critical assumptions are that the channel aspect ratio α is large; the reduced Reynolds number U * 0 W * /(ρµα 2 ) and Bond number Bo = ρgL * 2 /γ are small; the bubble occupies the full height of the channel; and the component of curvature as z varies corresponds to a semi-circle filling the channel height with the fluid perfectly wetting the upper and lower walls. We neglect the thin film corrections proposed by Homsy [22] and Reinelt [23], because they do not change the qualitative comparison with the experiment, and it is not obvious how they should be modified due to the presence of the depth-perturbation and multiple solutions [8][9][10]. The nondimensional domain is shown in figure 3.…”
Section: Governing Equationsmentioning
confidence: 99%
“…Figure 2(a) shows the bubble shape and speed for the first three solution branches in channels with a rectangular cross-section. Introducing a depth-perturbation to the system (see sketch in figure 1) allows the solution branches to interact, which results in the diverse range of observed stable steady states and time-dependent behaviour [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%